A angústia e a ficção contemporânea - Biziak, Jacob dos Santos; Gobbi, Marcia Valeria Zamboni [UNESP] (My University, 2013)
Our aim in this article is to accomplish an afterthought concerning contemporary fiction. Taken as initial the afterthought of the role of the novel as fiction and its linking with the afterthought of mimesis in modernity, we aim to consider the presence of agony not only as a theme but also as a structural element of narratives. Eventually, we will make brief tallies of theses aspects in the work of José Saramago.

Nosso objetivo, neste artigo, é realizar uma reflexão a respeito da ficção contemporânea. Tomando por começo a reconsideração do papel do romance como ficção e seu ligamento com a reconsideração da mímesis na modernidade, pretendemos pensar a presença do sentimento de angústia não somente como tema, mas também como elemento estrutural das narrativas. Por fim, faremos breves apontamentos sobre esses aspectos na obra de José Saramago.
Keywords: Agony; Fiction; Mimesis; José Saramago; Angústia; Ficção; Mímesis; José Saramago